Development and Field Test of New Environmentally Friendly Water-Rich Sand Grout Material - Wang Hongbo; Liu Rentai; Zhang Qingsong (Advances in Materials Science and Engineering)
The water-rich sand layer is a common source for underground engineering disasters. Considering the poor performance, high cost, and serious environmental pollution of conventional grouting materials, based on the requirements of environmental grouting treatment, a new type of environmental water-rich sand grouting material was proposed, which was mainly based on fly ash and cement and supplemented by water glass. The performance of the slurry was studied. The parameters such as the initial set time, the ratio of stone, and the compressive strength of the material under different water contents and fly ash contents were determined by experiments. The new grouting material was obtained with rapid setting, early strength, high ratio of stone formation, and strength, which were less affected by water content. The successful application of the new environmental grouting material in the Qingdao Metro not only ensures the safety of the project but also meets the requirements of environmental protection. It also verifies the scientificity of the material and will be useful for the innovation of the water-rich sand grouting material.